Circulating microRNAs as potential biomarkers for genetic generalized epilepsies: a three microRNA panel - Martins‐Ferreira, R. (2020)
Background and purpose: Genetic generalized epilepsies (GGEs) encompass a group of syndromes of mainly genetic causes, characterized by the involvement of both hemispheres. MicroRNAs (miRNAs) are small non-coding RNAs with a critical role in the regulation of neuronal biological processes through gene expression modulation. Dysregulated miRNA expression has been shown in epilepsy. Due to their stability in biological fluids like serum, miRNAs have assumed a prominent role in biomarker research. Our aim was to evaluate circulating levels of three miRNAs in GGE patients and assess their putative diagnostic value. Methods: MiR-146a, miR-155 and miR-132 were quantified by real-time polymerase chain reaction in the serum of 79 GGE patients (47 women, 32 men, 35.1 ± 12.4 years) and 67 healthy individuals (41 women, 26 men, 42.4 ± 10.1 years). Relative expression values were calculated using the 2-ΔΔCt method. Receiver operating characteristic curve analysis was performed to assess diagnostic value. MiRNA expression was correlated with clinicopathological features. Results: Serum levels of miR-146a and miR-155 were significantly upregulated in GGE patients relative to controls (3.13 and 6.05, respectively). Combined miR-146a, miR-155 and miR-132 serum levels performed well as a diagnostic biomarker, discriminating GGE patients from controls with an area under the curve of 0.85, 80% specificity and 73% sensitivity. Conclusions: Our results indicate that miR-146a, miR-155 and miR-132 may partake in GGE epileptogenesis. A panel of three circulating miRNAs with potential value as a GGE biomarker is reported for the first time. Novel biomarkers may help to identify new treatment targets and contribute to improved patients' quality of life through earlier diagnosis and a more precise prognosis.